Moisture-proof LED patch packaging adhesive and preparation method thereof

By reacting carronic anhydride with polycaprolactone triol and combining with alicyclic epoxy resin to form a polymer structure, the problem of insufficient moisture resistance of LED patch packaging glue in high temperature and high humidity environments is solved, and significant improvement in moisture resistance and product life is achieved.

CN119912904APending Publication Date: 2025-05-02HUIZHOU SHENGSHIDA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411797540.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing LED patch packaging glue has poor humidity resistance in high temperature and high humidity environments, resulting in excessive water absorption and cracked screens, limiting its application potential.

Method used

The substitution reaction between carronic anhydride and polycaprolactone triol forms an ester bond and reacts with alicyclic epoxy resin to form an ester bond and an oxidation ring, and graft the polycaprolactone polymer to enhance hydrophobicity.

Benefits of technology

It significantly improves the moisture resistance of LED patch packaging glue, extends the service life of the product, and maintains good performance in high and low temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177172180000121
    Figure BDA0005177172180000121
  • Figure FDA0005177172170000011
    Figure FDA0005177172170000011
Patent Text Reader

Abstract

According to the moisture-proof LED patch packaging adhesive and the preparation method thereof, alicyclic epoxy resin is adopted to replace traditional bisphenol A epoxy resin, caronic anhydride is used as a grafting medium, a macromolecular structure of polycaprolactone trihydric alcohol is bonded to the alicyclic epoxy resin, polycaprolactone macromolecules have a good hydrophobic property, and the moisture-proof LED patch packaging adhesive has a good moisture-proof effect. The molecular structure contains a large number of non-polar or low-polar parts, and the interaction force between the non-polar or low-polar parts and water molecules is weak, so that the water molecules are difficult to permeate. The crosslinking density of molecules of the cured product is remarkably improved, the moisture resistance, the hardness and the thermal deformation temperature of the product are improved, the LED patch packaging adhesive is not prone to cracking, and the service life of the product is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of epoxy adhesive preparation, in particular to moisture-resistant LED patch packaging adhesive and a preparation method thereof. Background Art

[0002] As a new generation of solid-state light source technology, LED has led the trend of innovation in lighting technology with its highly integrated structure and high color rendering index (CRI). However, as LED develops towards a trend of small pitch, a series of technical challenges have followed, and the requirements for LED chip encapsulation adhesives have become increasingly higher. The current mainstream LED chip encapsulation materials are mainly epoxy resin-based encapsulation adhesives, which have the advantages of low cost, good transparency and mature processing technology. However, traditional chip encapsulation materials have defects such as poor thermal stability and high moisture absorption rate. When dealing with high temperature and high humidity working environments, the existing epoxy resin encapsulation adhesive system generally faces the problem of poor product moisture resistance, which absorbs a lot of water and causes the screen to crack. Especially outdoors, it will cause the LED to become water-permeable and scrapped. This not only significantly shortens the service life of the product, but also greatly limits its application potential in a wider range of fields.

[0003] Exploring LED chip encapsulation adhesive systems with good moisture resistance has become the key to solving the above problems. Invention patents CN102634290A and CN104371618A both disclose methods for preparing LED chip encapsulation adhesives, and both use silicone organic intermediates to enhance the hydrophobicity of the product. However, silicone organic intermediates will cause a large amount of anhydride curing agent to volatilize during the curing process, reducing the curing efficiency and sacrificing the hardness performance of the product. There is still room for improvement in practical applications. Summary of the invention

[0004] In view of the above problems, the present invention provides a moisture-resistant LED chip encapsulation adhesive and a preparation method thereof. Caron anhydride and polycaprolactone triol undergo a substitution reaction to form an ester bond, and then the caron anhydride reacts with alicyclic epoxy resin to form an ester bond and an oxidized ring, so that the alicyclic resin can be grafted with a large amount of polycaprolactone polymer, thereby enhancing the hydrophobicity of the LED chip encapsulation adhesive.

[0005] A moisture-resistant LED patch encapsulation adhesive, the LED patch encapsulation adhesive comprises component A and component B, wherein, by weight, component A comprises 90-110 parts of alicyclic epoxy resin, 1-3 parts of caron anhydride, and 10-30 parts of polycaprolactone triol, and component B comprises 10-12 parts of silicon-modified alcohol and 100-110 parts of anhydride curing agent, wherein the components of silicon-modified alcohol comprise 80-110 parts of polycaprolactone triol, 8-11 parts of modified organic silicone resin, and 0.1-0.5 parts of phthalate coupling agent. Caron anhydride is used as a grafting medium, and the polycaprolactone polymer structure of the polycaprolactone triol is bonded to the alicyclic epoxy resin. The polymer structure contains a large amount of non-polar or low-polar parts, and the interaction force between the polymer and water molecules is weak, making it difficult to form a bond, resulting in difficulty for water molecules to penetrate, forming a good hydrophobic property, so that the product has a higher cross-linking density after curing, and the moisture resistance of the product is enhanced structurally.

[0006] Preferably, the molecular formula of the polycaprolactone triol is Wherein l, m, and n are all positive integers, and the molecular weight of polycaprolactone triol is 500-600. The high molecular polymer structure of polycaprolactone can increase the molecular cross-linking density of the product, and improve the anti-aging, weather resistance, high and low temperature resistance and other properties of the encapsulation glue.

[0007] Preferably, the anhydride curing agent includes one or more of methyl hexahydrophthalic anhydride and hexahydrophthalic anhydride. During the reaction and curing process of the anhydride curing agent and the alicyclic epoxy resin, the carboxyl group of the curing agent first reacts with the hydroxyl group of the epoxy resin to form a monoester, and then reacts with the hydroxyl group of other epoxy resins to form a diester, and the epoxy resin molecules are connected into a network structure by forming ester bonds, laying the foundation for the cross-linked structure.

[0008] Preferably, the modified silicone resin includes one or more of methylphenyl polysiloxane resin, acrylic modified silicone resin, and methylphenyl silicone resin. The structure of the modified silicone resin contains silicon-oxygen bonds, which have a large bond energy and can stabilize the molecular structure of the resin, making it less prone to bond breaking and degradation, thereby enhancing the thermal stability of the product. At the same time, silicon-oxygen bonds are hydrophobic, and grafting them into epoxy resins will reduce the product's affinity for water molecules and improve the product's moisture resistance.

[0009] Preferably, the alicyclic epoxy resin includes alicyclic epoxy resin 2121P, alicyclic epoxy resin EHPE3150, and alicyclic epoxy resin AT26. The epoxy group of the alicyclic epoxy resin is directly connected to the alicyclic ring to form a tight rigid oxide ring structure, so that the cross-linking density of the molecule is increased after curing, the cured encapsulation glue has a higher thermal denaturation temperature, and the high temperature resistance of the product is enhanced. At the same time, the alicyclic epoxy resin does not contain a benzene ring, which reduces the hygroscopicity of the product.

[0010] A method for preparing a moisture-resistant LED chip encapsulation adhesive, characterized in that it comprises the following steps:

[0011] Mix alicyclic epoxy resin, caron anhydride and polycaprolactone polytriol according to weight proportion, stir and react under vacuum, and filter to obtain component A;

[0012] According to the weight proportion, polycaprolactone polytriol, modified silicon organic intermediate and phthalate coupling agent are mixed and dissolved, heated and stirred under vacuum to obtain silicon-modified alcohol; silicon-modified alcohol is prepared to replace the direct addition of modified silicon organic intermediate, the solubility of alcohol is stronger than that of organic intermediate, the reaction time can be reduced and the reaction temperature can be lowered, the volatilization of anhydride curing agent during the curing process can be significantly reduced, the curing efficiency can be improved, and the moisture resistance of the product can be improved.

[0013] The silicon-modified alcohol and the anhydride curing agent are mixed uniformly according to the weight ratio, and filtered to obtain component B;

[0014] Component A and component B are mixed in a weight ratio of 100:100-110, and dispersed under vacuum to obtain a moisture-resistant LED chip encapsulation adhesive. Slightly increasing the proportion of component B curing agent can ensure that the product is fully cured and avoid uneven curing.

[0015] Preferably, the temperature of the mixed stirring reaction is 115-125° C., the reaction time is 6-10 hours, and the stirring speed is 500-800 rpm / min. High temperature provides sufficient activation energy for the esterification reaction of caron anhydride with polycaprolactone triol and the reaction of caron anhydride with alicyclic epoxy resin. High-speed stirring increases the contact between different reaction substances, improves the uniformity and reaction efficiency of the reaction, and the reaction time is controlled to be 6-10 hours because the raw materials are basically fully converted during this period of time, and the product purity is relatively high.

[0016] Preferably, the temperature of the mixed dissolution is 70-80° C., and the dissolution time is 1 hour. The slow dissolution at low temperature can reduce the volatilization of polycaprolactone triol and increase the reaction output.

[0017] Preferably, the temperature of the heating and stirring is 135-145°C, the time is 5-6 hours, and the stirring speed is 60-100rpm / min. The polycaprolactone triol and the modified silicon organic intermediate react under the catalysis of the phthalate coupling agent. The catalytic efficiency of the phthalate coupling agent is best under the condition of 135-145°C. The low-speed stirring can avoid the agglomeration of the reaction product. The reaction time is controlled to 5-6 hours to avoid excessive reaction to produce a large number of by-products affecting the purity of the product.

[0018] Preferably, the mixing and dispersing time is 6-10 minutes. Sufficient dispersion can make component A and component B evenly mixed, avoiding the problem of uneven curing of the product during use.

[0019] Preferably, the vacuum pressure is -0.1 MPa. The purpose of vacuum treatment is to degas the product. Oxygen cannot be avoided from entering the product during the reaction. If the degassing process is missing, the final product will be slowly oxidized and inactivated during storage due to the presence of oxygen, which will shorten the storage time of the product and affect the use of the product.

[0020] Compared with the prior art, the beneficial effect of the present invention is that the polymer structure of polycaprolactone triol contains a large amount of non-polar or low-polar parts, and the interaction force between the polycaprolactone triol and the water molecules is weak, and it is difficult for the water molecules to penetrate into the structure, forming a good hydrophobic property. The reaction of the alicyclic resin and the polycaprolactone triol uses caron anhydride as a grafting medium, wherein one carboxyl group of the caron anhydride first undergoes an esterification reaction with the hydroxyl group of the alicyclic epoxy resin to form an ester bond, and the other carboxyl group reacts with the hydroxyl group of the polycaprolactone triol to form an ester bond. With caron anhydride as the basic structure, the polycaprolactone polymer structure is bonded to the alicyclic epoxy resin through two ester bonds. The alicyclic epoxy resin carrying the polycaprolactone polymer structure has good hydrophobicity, reduced hygroscopicity, and improved moisture resistance, so that the LED chip encapsulation glue is not easy to crack in a humid environment, thereby extending the service life of the product.

[0021] The epoxy group of the alicyclic epoxy resin used in the present invention is directly connected to the alicyclic ring, which can form a tight rigid oxidized ring structure, improve the hardness and thermal deformation temperature of the product, and significantly improve the cross-linking density of the product molecules after curing. In addition, the present invention uses silicon-modified alcohol instead of directly adding silicon organic intermediates in the prior art, which reduces the volatilization of the acid anhydride curing agent during the curing process and improves the access rate of silicon-oxygen bonds in the LED chip packaging glue molecules. DETAILED DESCRIPTION

[0022] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and essence of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention all belong to the scope of protection of the present invention. Unless otherwise specified, the experimental materials, reagents, instruments, etc. used in the examples of the present invention are all commercially available; unless otherwise specified, all technical means in the examples of the present invention are conventional means well known to those skilled in the art.

[0023] Example 1

[0024] Weigh 90 parts of alicyclic epoxy resin 2121P, 1 part of caronic anhydride, and 10 parts of polycaprolactone triol 3057, pour all into a four-necked flask, place it in an environment of 120°C, set the vacuum pressure to -0.1 MPa, stir and react at a rate of 800 rpm / min under vacuum for 10 hours, and filter the product impurities to obtain component A.

[0025] Weigh components including 100 parts of polycaprolactone triol 3057, 9 parts of methylphenyl polysiloxane resin SH-3047, and 0.1 parts of phthalate coupling agent, pour all into a four-necked flask, place in an environment of 80° C., and dissolve for 1 hour.

[0026] After sufficient dissolution, the four-necked flask was transferred to an environment of 140° C. and stirred at a rate of 100 rpm / min under vacuum for 6 hours to obtain silicon-modified alcohol.

[0027] 12 parts of silicon-modified alcohol and 100 parts of methylhexahydrophthalic anhydride were mixed evenly, and then filtered to obtain component B.

[0028] 100 parts of component A and 110 parts of component B were mixed evenly, and the vacuum pressure was set to -0.1 MPa. The mixture was dispersed in a vacuum state for 10 minutes to obtain a moisture-resistant LED chip encapsulation adhesive.

[0029] Example 2

[0030] Weigh 95 parts of alicyclic epoxy resin 2121P, 1 part of caronic anhydride, and 10 parts of polycaprolactone triol 3057, pour all into a four-necked flask, place it in an environment of 120°C, set the vacuum pressure to -0.1 MPa, stir and react at a rate of 800 rpm / min under vacuum for 10 hours, and filter the product impurities to obtain component A.

[0031] Weigh components including 100 parts of polycaprolactone triol 3057, 9 parts of methylphenyl polysiloxane resin SH-3047, and 0.1 parts of phthalate coupling agent, pour all into a four-necked flask, place in an environment of 80° C., and dissolve for 1 hour.

[0032] After sufficient dissolution, the four-necked flask was transferred to an environment of 140° C. and stirred at a rate of 100 rpm / min under vacuum for 6 hours to obtain silicon-modified alcohol.

[0033] 12 parts of silicon-modified alcohol and 100 parts of methylhexahydrophthalic anhydride were mixed evenly, and then filtered to obtain component B.

[0034] 100 parts of component A and 110 parts of component B were mixed evenly, and the vacuum pressure was set to -0.1 MPa. The mixture was dispersed in a vacuum state for 10 minutes to obtain a moisture-resistant LED chip encapsulation adhesive.

[0035] Example 3

[0036] Weigh 100 parts of alicyclic epoxy resin 2121P, 1.5 parts of caronic anhydride, and 15 parts of polycaprolactone triol 3057, pour all into a four-necked flask, place it in an environment of 120°C, set the vacuum pressure to -0.1 MPa, stir and react at a rate of 800 rpm / min under vacuum for 10 hours, and filter the product impurities to obtain component A.

[0037] Weigh components including 100 parts of polycaprolactone triol 3057, 9 parts of methylphenyl polysiloxane resin SH-3047, and 0.1 parts of phthalate coupling agent, pour all into a four-necked flask, place in an environment of 80° C., and dissolve for 1 hour.

[0038] After sufficient dissolution, the four-necked flask was transferred to an environment of 140° C. and stirred at a rate of 100 rpm / min under vacuum for 6 hours to obtain silicon-modified alcohol.

[0039] 12 parts of silicon-modified alcohol and 100 parts of methylhexahydrophthalic anhydride were mixed evenly, and then filtered to obtain component B.

[0040] 100 parts of component A and 110 parts of component B were mixed evenly, and the vacuum pressure was set to -0.1 MPa. The mixture was dispersed in a vacuum state for 10 minutes to obtain a moisture-resistant LED chip encapsulation adhesive.

[0041] Example 4

[0042] Weigh 105 parts of alicyclic epoxy resin 2121P, 1.5 parts of caronic anhydride, and 15 parts of polycaprolactone triol 3057, pour all into a four-necked flask, place it in an environment of 120°C, set the vacuum pressure to -0.1 MPa, stir and react at a rate of 800 rpm / min under vacuum for 10 hours, and filter the product impurities to obtain component A.

[0043] Weigh components including 100 parts of polycaprolactone triol 3057, 9 parts of methylphenyl polysiloxane resin SH-3047, and 0.1 parts of phthalate coupling agent, pour all into a four-necked flask, place in an environment of 80° C., and dissolve for 1 hour.

[0044] After sufficient dissolution, the four-necked flask was transferred to an environment of 140° C. and stirred at a rate of 100 rpm / min under vacuum for 6 hours to obtain silicon-modified alcohol.

[0045] 12 parts of silicon-modified alcohol and 100 parts of methylhexahydrophthalic anhydride were mixed evenly, and then filtered to obtain component B.

[0046] 100 parts of component A and 110 parts of component B were mixed evenly, and the vacuum pressure was set to -0.1 MPa. The mixture was dispersed in a vacuum state for 10 minutes to obtain a moisture-resistant LED chip encapsulation adhesive.

[0047] Example 5

[0048] Weigh 110 parts of alicyclic epoxy resin 2121P, 2 parts of caronic anhydride, and 20 parts of polycaprolactone triol 3057, pour all into a four-necked flask, place it in an environment of 120°C, set the vacuum pressure to -0.1 MPa, stir and react at a rate of 800 rpm / min under vacuum for 10 hours, and filter the product impurities to obtain component A.

[0049] Weigh components including 100 parts of polycaprolactone triol 3057, 9 parts of methylphenyl polysiloxane resin SH-3047, and 0.1 parts of phthalate coupling agent, pour all into a four-necked flask, place in an environment of 80° C., and dissolve for 1 hour.

[0050] After sufficient dissolution, the four-necked flask was transferred to an environment of 140° C. and stirred at a rate of 100 rpm / min under vacuum for 6 hours to obtain silicon-modified alcohol.

[0051] 12 parts of silicon-modified alcohol and 100 parts of methylhexahydrophthalic anhydride were mixed evenly, and then filtered to obtain component B.

[0052] 100 parts of component A and 110 parts of component B were mixed evenly, and the vacuum pressure was set to -0.1 MPa. The mixture was dispersed in a vacuum state for 10 minutes to obtain a moisture-resistant LED chip encapsulation adhesive.

[0053] Comparative Example 1

[0054] Weigh 100 parts of bisphenol A epoxy resin, 1 part of caronic anhydride, and 10 parts of polycaprolactone triol 3057, pour all into a four-necked flask, place it in an environment of 120°C, set the vacuum pressure to -0.1 MPa, stir and react at a rate of 800 rpm / min under vacuum for 10 hours, and filter the product impurities to obtain component A.

[0055] Weigh components including 100 parts of polycaprolactone triol 3057, 9 parts of methylphenyl polysiloxane resin SH-3047, and 0.1 parts of phthalate coupling agent, pour all into a four-necked flask, place in an environment of 80° C., and dissolve for 1 hour.

[0056] After sufficient dissolution, the four-necked flask was transferred to an environment of 140° C. and stirred at a rate of 100 rpm / min under vacuum for 6 hours to obtain silicon-modified alcohol.

[0057] 12 parts of silicon-modified alcohol and 100 parts of methylhexahydrophthalic anhydride were mixed evenly, and then filtered to obtain component B.

[0058] Take 100 parts of component A and 110 parts of component B, mix them evenly, set the vacuum pressure to -0.1 MPa, and disperse them in a vacuum state for 10 minutes to obtain an LED chip encapsulation adhesive.

[0059] Comparative Example 2

[0060] Weigh 90 parts of alicyclic epoxy resin 2121P and 1 part of caronic anhydride, pour all into a four-necked flask, place it in an environment of 120° C., set the vacuum pressure to -0.1 MPa, stir and react at a rate of 800 rpm / min under vacuum for 10 hours, and filter the product impurities to obtain component A.

[0061] Weigh components including 100 parts of polycaprolactone triol 3057, 9 parts of methylphenyl polysiloxane resin SH-3047, and 0.1 parts of phthalate coupling agent, pour all into a four-necked flask, place in an environment of 80° C., and dissolve for 1 hour.

[0062] After sufficient dissolution, the four-necked flask was transferred to an environment of 140° C. and stirred at a rate of 100 rpm / min under vacuum for 6 hours to obtain silicon-modified alcohol.

[0063] 12 parts of silicon-modified alcohol and 100 parts of methylhexahydrophthalic anhydride were mixed evenly, and then filtered to obtain component B.

[0064] Take 100 parts of component A and 110 parts of component B, mix them evenly, set the vacuum pressure to -0.1 MPa, and disperse them in a vacuum state for 10 minutes to obtain an LED chip encapsulation adhesive.

[0065] Comparative Example 3

[0066] Weigh 90 parts of alicyclic epoxy resin 2121P, 1 part of caronic anhydride, and 10 parts of polycaprolactone triol 3057, pour all into a four-necked flask, place it in an environment of 120°C, set the vacuum pressure to -0.1 MPa, and stir the reaction at a rate of 800 rpm / min under vacuum for 10 hours.

[0067] The reaction product was placed in a vacuum degassing machine, the vacuum pressure was set to -0.1 MPa, vacuum treated for 20 minutes, and the product impurities were filtered to obtain component A.

[0068] Take 12 parts of methylphenyl polysiloxane resin SH-3047 and 100 parts of methylhexahydrophthalic anhydride, mix them evenly, and filter to obtain component B.

[0069] Take 100 parts of component A and 110 parts of component B, mix them evenly, set the vacuum pressure to -0.1 MPa, and disperse them in a vacuum state for 10 minutes to obtain an LED chip encapsulation adhesive.

[0070] Experimental example

[0071] The LED chip encapsulation adhesive obtained in the embodiment and the comparative example is encapsulated on the LED chip, put into an oven, first set the temperature to 120° C. and bake for 4 hours, then increase the temperature to 150° C. and bake for 3 hours to obtain a cured LED chip encapsulation adhesive.

[0072] The glass transition temperature (TG), hardness, heat deformation temperature, refractive index, hygroscopicity, high and low temperature resistance, reflow soldering cracking and other properties of the cured LED chip encapsulation adhesive obtained in the test examples and comparative examples are tested. The test methods for various performance indicators are as follows:

[0073] The test standard for glass transition temperature (TG) refers to GB / T 19466.2-2004.

[0074] The test standard for hardness refers to GB / T 531.1-2008.

[0075] The test standard for heat deformation temperature refers to GB / T1634-1979.

[0076] Refractive index test method: At room temperature, place the cured LED chip encapsulation glue on a refractometer and use sodium light D line to test the refractive index of the product.

[0077] Moisture resistance test method: Set the constant temperature and humidity test chamber to 85℃ and 85% relative humidity, preheat and stabilize to the set value, place the cured LED patch packaging glue in the test chamber, start the test chamber, process for 48 hours, quickly transfer the product to 225℃ reflow soldering, and observe the cracking of the LED patch under an electron microscope. Patch cracking means that the product has poor moisture resistance.

[0078] High and low temperature resistance test method: Set the temperature range of the hot and cold shock test box to -40℃-120℃, the exposure time is 30 minutes, and the number of cycles is 300 times. After the treatment, test the luminescence of the LED patch within 300 times. If the patch does not emit light, it means that the product has poor weather resistance in extreme environments.

[0079] The performance test results are shown in Table 1.

[0080] Table 1 LED chip packaging adhesive performance test results

[0081]

[0082] It can be seen from the embodiments that the LED patch packaging glue obtained by the preparation method provided by the present invention has a hardness greater than 80 and a high heat deformation temperature. The LDE patch will basically not be dark under hot and cold shocks, indicating that the product has a high resistance to high and low temperatures and can maintain a high hardness. After the double 85 test and the reflow soldering at 225°C, the product did not crack, indicating that the product has good moisture resistance and low hygroscopicity. The comprehensive hardness, temperature resistance, moisture resistance and other performances indicate that the product has good anti-aging ability and extended service life. At the same time, the refractive index of the product in the embodiments is greater than 1.6, indicating that the product will not affect the color rendering of the LED patch.

[0083] Compared with Comparative Example 1, Example 1 shows that the use of alicyclic epoxy resin instead of bisphenol A epoxy resin can significantly improve the hardness of the product, prevent the encapsulation glue from cracking, and have good tolerance performance; Compared with Comparative Example 2, Example 1 shows that the lack of high-molecular access of polycaprolactone triol will reduce the moisture resistance of the product, causing the product to be easy to crack, and the hardness, thermal deformation temperature, etc. are reduced; Compared with Comparative Example 3, Example 1 shows that the use of silicon-modified alcohol has higher curing efficiency and better effect than directly adding silicon organic intermediates.

[0084] Based on the above experimental results, the LED chip encapsulation adhesive of the present invention has low moisture absorption rate, strong hydrophobicity, and basically no cracking when used in a humid environment, and the product has a long service life. At the same time, it has high hardness and thermal deformation temperature, and has good adaptability to extreme ambient temperatures such as high and low temperatures. The preparation process of the product is simple, the practicability is strong, and it has the conditions for large-scale production.

[0085] It can be understood that the above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, the above technical features can be freely combined without departing from the concept of the present invention, and several deformations and improvements can be made, which all belong to the protection scope of the present invention. Therefore, all equivalent changes and modifications made to the scope of the claims of the present invention should belong to the coverage of the claims of the present invention.

Claims

1. A moisture-resistant LED chip encapsulation adhesive, characterized in that: The LED chip encapsulation adhesive comprises, by weight, 90-110 parts of alicyclic epoxy resin, 1-3 parts of caron anhydride, 10-30 parts of polycaprolactone triol, 10-12 parts of silicon-modified alcohol, and 100-110 parts of anhydride curing agent.

2. The LED chip encapsulation adhesive according to claim 1, characterized in that: The components of the silicon-modified alcohol include, by weight, 80-110 parts of polycaprolactone triol, 8-11 parts of modified organic silicone resin, and 0.1-0.5 parts of phthalate coupling agent.

3. The LED chip encapsulation adhesive according to claim 1, characterized in that: The molecular formula of the polycaprolactone triol is Wherein l, m, and n are all positive integers, and the molecular weight of the polycaprolactone triol is 500-600.

4. The LED chip encapsulation adhesive according to claim 1, characterized in that: The acid anhydride curing agent includes one or more of methyl hexahydrophthalic anhydride and hexahydrophthalic anhydride.

5. The LED chip encapsulation adhesive according to claim 1, characterized in that: The modified silicone resin includes one or more of methylphenyl polysiloxane resin, acrylic modified silicone resin, and methylphenyl silicone resin.

6. The LED chip encapsulation adhesive according to claim 1, characterized in that: The alicyclic epoxy resin includes alicyclic epoxy resin 2121P, alicyclic epoxy resin EHPE3150, and alicyclic epoxy resin AT26.

7. A method for preparing the moisture-resistant LED chip encapsulation adhesive according to claim 1, characterized in that: The following steps are involved: Mix alicyclic epoxy resin, caron anhydride and polycaprolactone polytriol according to weight proportion, stir and react under vacuum, and filter to obtain component A; Mix and dissolve polycaprolactone polytriol, modified silicon organic intermediate and phthalate coupling agent according to weight proportion, heat and stir under vacuum to obtain silicon-modified alcohol; The silicon-modified alcohol and the anhydride curing agent are mixed uniformly according to the weight ratio, and filtered to obtain component B; Component A and component B are mixed in a weight ratio of 100:100-110, and dispersed in a vacuum state to obtain an LED chip encapsulation adhesive suitable for small spacing.

8. The preparation method according to claim 7, characterized in that: The temperature of the mixed stirring reaction is 115-125° C., the reaction time is 6-10 hours, and the stirring speed is 500-800 rpm / min.

9. The preparation method according to claim 7, characterized in that: The temperature of the mixed dissolution is 70-80° C., and the dissolution time is 1 hour.

10. The preparation method according to claim 7, characterized in that: The heating and stirring temperature is 135-145° C., the time is 5-6 hours, and the stirring speed is 60-100 rpm / min.

11. The preparation method according to claim 7, characterized in that: The mixing and dispersing time is 6-10 minutes.

12. The preparation method according to claim 7, characterized in that: The vacuum pressure is -0.1 MPa.

Citation Information

Patent Citations

  • Double-component transparent epoxy resin LED (light emitting diode) patch packing adhesive

    CN102634290A

  • Dampness and heat resistant low light decay transparent epoxy LED encapsulating glue and preparation thereof

    CN104371618A